A review on real-time implantable and wearable health monitoring sensors based on triboelectric nanogenerator approach. (February 2021) - Mathew, Ammu Anna; Chandrasekhar, Arunkumar; Vivekanandan, S.
Abstract: The recent developments in the promising technology, Triboelectric Nanogenerators (TENGs) have brought numerous changes in the medical field. The amalgamation of triboelectric effect with electrostatic induction leads to electricity generation in this novel technology, TENG. TENGs can harvest different types of mechanical energies and convert it to electrical energy, thereby enabling self-powered operations for different systems. The recent advancement in the implantable and wearable TENGs plays a vital role in the daily life of humans from in vitro to in vivo treatments. An introduction to nanogenerators (NG), especially focusing on TENG and different modes of TENG operations, is made initially. Besides, a description of the different materials used for device fabrication to create triboelectric effect and criteria to select the materials to enhance the triboelectrification is also done. An overview on TENG applications in different medical fields are explained highlighting mainly on the materials and structure utilized in the device to develop the triboelectrification effect. Here the biomedical fields considered were mainly classified into ten different categories with certain sub-categories which include cell modulation, drug delivery, circulatory system, hair regeneration, neural prosthesis, biodegradable electronics, gene delivery, microbial disinfection, health monitoring and implantable devices. The methods and structures employed in certain devices to enhance the sensitivity are also mentioned and in all the devices considered in this review human body motion and their physical activities is the driving force. An illustration of the existing challenges faced and a futuristic overview of stretchable and wearable sensing platforms based on TENG for healthcare applications is done in this review. Graphical Abstract: ga1 Highlights: The fundamental modes of operation of triboelectric nanogenerators and materials with triboelectric properties are explained. Triboelectric materials directly convert mechanical energy into electricity without any external input. The review is structured by classifying the TENG applications into different fields. This review is focusing mainly on the sensor materials, device structure and its output for real-time health monitoring. A viewpoint on existing challenges and future explorations are discussed.